Power Inequality and Conflict: Cases of Abuse and Violence Within the Transgender Community in India - Nibedita Dubey; Manosmita Mahapatra (Journal of Psychosexual Health)
Transgender individuals, often marginalized and stigmatized by broader society, turn to the transgender communities for support. However, the centralization of power and authority in the hands of the Guru forces the Chela or followers to live a life of bonded labor. The present study intends to investigate and comprehend the challenges transgender women face within their community incorporating verbal, psychological, physical, financial, and sexual abuse inculcating an understanding from the sociological perspective of power relations. The aim of the study is accomplished through using both primary and secondary data. The study utilizes both quantitative and qualitative data, with a sample size of 150 drawn from three districts in Odisha. The findings suggest that respondents living within the transgender community face several acts of violence and abuse by other transgender. From the several acts of abuse, verbal abuse is the most prevalent form of violence within communities. Hence, the transgenders stand strangled in multiple marginalities and face cumulative violence in society, within their community, and from their rival transgender groups.